Warming enhances lanthanum accumulation and toxicity promoting cellular damage in glass eels (Anguilla anguilla) - Figueiredo, Cátia (2020)
Cumulative and continuing human emissions of greenhouse gases to the atmosphere are causing ocean warming. Rising temperature is a major threat to aquatic organisms and may affect physiological responses, such as acid-base balance, often compromising species fitness and survival. It is also expected that warming may influence the availability and toxicological effects of pollutants, including Rare Earth Elements. These are contaminants of environmental emerging concern with great economic interest. This group comprises yttrium, scandium and lanthanides, being Lanthanum (La) one of the most common. The European eel (Anguilla anguilla) is critically endangered and constitutes a delicacy in South East Asia and Europe, being subject to an increasing demand on a global scale. Considering the vulnerability of early life stages to contaminants, we exposed glass eels to 1.5 μg L-1 of La for five days, plus five days of depuration, under a present-day temperature and warming scenarios (△T = +4 °C). The aim of this study was to assess the bioaccumulation, elimination and specific biochemical enzymatic endpoints in glass eels (Anguilla anguilla) tissues, under warming and La. Overall, our results showed that the accumulation and toxicity of La were enhanced with increasing temperature. The accumulation was higher in the viscera, followed by the head, and ultimately the body. Elimination was less effective under warming. Exposure to La did not impact acetylcholinesterase activity. Moreover, lipid peroxidation peaked after five days under the combined exposure of La and warming. The expression of heat shock proteins was majorly suppressed in glass eels exposed to La, at both tested temperatures. This result suggests that, when exposed to La, glass eels were unable to efficiently prevent cellular damage, with a particularly dramatic setup in a near-future scenario. Further studies are needed towards a better understanding of the effects of lanthanum in a changing world.